2023
DOI: 10.1287/mnsc.2022.4622
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Nudges on User-Generated Content for Social Network Platforms

Abstract: Content-sharing social network platforms rely heavily on user-generated content to attract users and advertisers, but they have limited authority over content provision. We develop an intervention that leverages social interactions between users to stimulate content production. We study social nudges, whereby users connected with a content provider on a platform encourage that provider to supply more content. We conducted a randomized field experiment (N [Formula: see text]) on a video-sharing social network p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Another set of concerns involves the possibility that the effectiveness of messagebased nudges may decrease over time (Zeng et al, 2023). Moreover, especially if the nudges are repeated too frequently, there is the potential for user desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Another set of concerns involves the possibility that the effectiveness of messagebased nudges may decrease over time (Zeng et al, 2023). Moreover, especially if the nudges are repeated too frequently, there is the potential for user desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the second approach relies on leveraging online signals such as awards (Foerderer et al. , 2021; Gallus, 2017) and social nudges to guide contribution behavior (Zeng et al. , 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The first approach leans toward hard management strategies, including control measures (Kapoor and Agarwal, 2017), boundary resources (Ghazawneh and Henfridsson, 2013) and competitive tactics (Foerderer et al, 2018). In contrast, the second approach relies on leveraging online signals such as awards (Foerderer et al, 2021;Gallus, 2017) and social nudges to guide contribution behavior (Zeng et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Regarding the latter, it would be valuable to investigate whether implementing an idea browsing approach following the general architecture suggested in this article would actually result in a higher number of contributions. The integration of nudges into representations of ideas would also be interesting to study, as previous research showed that nudges can increase contributions on user-generated content platforms [52].…”
Section: Future Workmentioning
confidence: 99%